Modeling the Resilience of Power Distribution Systems Against Extreme Winds by Considering Falling Trees - Guangyang, H.; Muraleetharan, K.K. (University of Jaffna, 2022)
Overhead electrical power distribution systems (PDS) are very susceptible to extreme wind events such as hurricanes and typhoons. Power outages can cause catastrophic consequences, including economic loss, loss of other critical services, and disruption of daily life. Therefore, it is very important to model the resilience of PDS against extreme winds to support disaster planning. Although falling trees are one of the main causes of PDS failures, the tree-failure risk was rarely considered in the performance assessment of PDS in the literature. In this study, a probabilistic simulation framework is proposed to model the resilience of PDS against extreme winds, in which the tree-failure risk can be realistically considered. The framework is demonstrated with a power distribution network in Oklahoma. Results show that the system resilience can reduce by 24% if tree failures are considered. In addition, crown thinning can effectively enhance the system resilience but will become less effective when the wind speed is very low or high.
Keywords: Resilience; Enhancement; Power distribution system; Fragility; Falling trees; Crown thinning